MAE solar car project : suspension - endurance - Chew, Zi Xiong. (2009)
The report summarizes the author’s work in redesigning the solar car suspension components and performing analysis and simulation tests on the new suspension assembly. It is a continuation of the previous Final Year Project report to build and design a solar car to represent Nanyang Technological University (NTU) to compete in the upcoming biannual World Solar Challenge (WSC) in 25th October 2009.